Optimization of the production of ethyl esters by ultrasound assisted reaction of soybean oil and ethanol - Rodrigues,S. (2009)
Biodiesel is a renewable liquid fuel that can be produced by a transesterification reaction between a vegetable oil and an alcohol. This paper evaluates and optimizes the production of ethyl esters (biodiesel) from soybean oil and ethanol. The reaction was carried out by applying ultrasound under atmospheric pressure and ambient temperature. Response surface methodology was used to evaluate the influence of alcohol to oil molar ratio and catalyst concentration on the yield of conversion of soybean oil into ethyl esters. The process resulted in a maximum yield of 91.8% after 30 minutes of reaction. The process variables alcohol to oil ratio and catalyst to oil ratio were statistically significant regarding the yield of ethyl esters. The optimal operating condition was obtained applying an alcohol to oil molar ratio of 10.2 and a catalyst to oil weight ratio of 0.0035.